Intraflagellar transport genes are essential for differentiation and survival of vertebrate sensory neurons - Tsujikawa, Motokazu; Malicki, Jarema (Neuron (Cambridge, Mass.), 2004)
Cilia play diverse roles in vertebrate and invertebrate sensory neurons. We show that a mutation of the zebrafish oval (ovl) locus affects a component of the ciliary transport (IFT) mechanism, the IFT88 polypeptide. In mutant retina, cilia are generated but not maintained, producing the absence of photoreceptor outer segments. A loss of cilia also occurs in auditory hair cells and olfactory sensory neurons. In all three sense organs, cilia defects are followed by degeneration of sensory cells. Similar phenotypes are induced by the absence of the IFT complex B polypeptides, ift52 and ift57, but not by the loss of complex A protein, ift140. The degeneration of mutant photoreceptor cells is caused, at least partially, by the ectopic accumulation of opsins. These studies reveal an essential role for IFT genes in vertebrate sensory neurons and implicate the molecular components of intraflagellar transport in degenerative disorders of these cells.